The Ecumenical and Non-Ecumenical Dialectic of Christian Bioethics - Wildes, Kevin Wm. (Christian bioethics, 1995)
Non-ecumenical Christian bioethics will seem a strange category for many. The category relies on the recognition that bioethics mediates morality and ethics in healthcare. As such bioethics will have particular content. It is the content of a moral vision that both divides and unites. The enterprise of non-ecumenical Christian bioethics explores how Christians are both divided and united on the issues of bioethics. Non-ecumenical Christian bioethics is opposed to a facile ecumenism that reduces the content of Christian morality to the lowest common denominator.